PSYCHOLOGICAL FEATURES OF COMMUNICATIVE COMPETENCE OF FUTURE PROFESSIONALS - Kazibekova, Viktoriia Fedorivna (Insight: the psychological dimensions of society, 2019)
Purpose: The article’s objective is to investigate empirically the psychological peculiarities of the formation of communicative competence in different professional groups. Methods: theoretical methods: (analysis, synthesis, comparison, generalization) were used to study the scientific literature on issues related to the category of “communicative competence”, empirical methods: “Questionnaire of Communicative Competence” by E.F. Zeer, E.E. Simanyuk, "Communicative Skills" by L. Michelson in the adaptation of Y.Z. Hilbuh; methods of quantitative and qualitative processing of results. Results. A theoretical analysis of approaches to the problem of communicative competence, success of professional activity has been made. Components of communicative competence have been considered. Communicative competence can be considered as an integral, relatively stable, holistic formation, manifested in the individual-psychological features of behavior and communication and includes a set of knowledge, experience, qualities, abilities of the individual, which allow to perform effectively communicative functions. The research has been attended by fourth-year cadets of the Odessa State University of Internal Affairs (30 people) and students psychologists of the fourth year of Kherson State University (30 people).The average age of the subjects was 22 years. We did not take into account sample composition by gender. Conclusions. Future psychologists have significantly more communicative competence than future police specialists. It includes the following components: social and communicative adaptability (they are more flexible in communication, able to interact with a variety of people, adapt to changing social circumstances), tolerance (more tolerant of others’ thoughts, attitudes, habits), frustration tolerance (resistance to life difficulties, self-regulation of emotional states). Also, graduate psychologists are statistically significantly more competent and less aggressive in professional interaction than graduate cadets.